Implementasi Nasab Anak di Luar Nikah terhadap Hukum Waris - Hammed, Nasem; Noviyanti, Noviyanti; Pebrizal, Aidi; Aditiya, Aditiya; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Based on the Civil Code, an illegitimate child who is not recognized by his father or mother is considered to have no legal relationship with his parents. However, if the illegitimate child is recognized and the recognition is accompanied by legalization, the child has the right to inherit the inheritance of the parents who recognize him, in accordance with the provisions of the distribution of inheritance regulated by law. According to Article 43 paragraph (1) of Marriage Law Number 1 of 1974, an illegitimate child who is not recognized still has a civil relationship with his mother and his mother's family. The rights of an illegitimate child who have been recognized and certified to the inheritance are the same as those of the legal child, making him an heir of an equal position. In civil law, the division of inheritance is regulated based on the applicable category of heirs.